Pendampingan Branding Produk UMKM Opak Singkong di Desa Cilimus Kecamatan Teluk Pandan Kabupaten Pesawaran Lampung - Nurmalia, Gustika; Astarika, Dela; H, Clarissa Novianti; Handayani, Ani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This community service activity aims to provide assistance to MSME actors in providing knowledge about product branding to increase buyer attraction and selling value of Opak Singkong MSMEs in Cilimus Village, Teluk Pandan District, Pesawaran Regency, Lampung. This activity is held through face-to-face training (On the spot training) with methods that include lectures, question and answer sessions, and assignments to participants. Product branding assistance is a very important effort in increasing buyer attraction and selling value of opaque cassava MSME products in Cilimus Village, Teluk Pandan District, Pesawaran Regency. Through this activity, MSME participants are given a better understanding of the importance of branding in building consumer trust in products. The result is an improvement in logo design that fits their brand and products, as well as the ability to market products more effectively.